2001
DOI: 10.1126/science.1059157
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Specific Transcriptional Regulation Through an IL-5Rα Interacting Protein

Abstract: Cytokine receptors consist of multiple subunits, which are often shared between different receptors, resulting in the functional redundancy sometimes observed between cytokines. The interleukin 5 (IL-5) receptor consists of an IL-5-specific alpha-subunit (IL-5Ralpha) and a signal-transducing beta-subunit (betac) shared with the IL-3 and granulocyte-macrophage colony-stimulating factor (GM-CSF) receptors. In this study, we sought to find a role for the cytoplasmic domain of IL-5Ralpha. We show that syntenin, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 18 publications
6
89
0
1
Order By: Relevance
“…We have previously reported that the adapter protein syntenin, also known as MDA-9, associates with Sox4 (Lin et al, 1998;Geijsen et al, 2001). Endogenous syntenin and Sox4 expression levels appear to correlate to some degree, particularly upon Mg132 treatment (Figure 1d).…”
Section: Syntenin Regulates Sox4 Protein Expression By Association Wimentioning
confidence: 76%
See 4 more Smart Citations
“…We have previously reported that the adapter protein syntenin, also known as MDA-9, associates with Sox4 (Lin et al, 1998;Geijsen et al, 2001). Endogenous syntenin and Sox4 expression levels appear to correlate to some degree, particularly upon Mg132 treatment (Figure 1d).…”
Section: Syntenin Regulates Sox4 Protein Expression By Association Wimentioning
confidence: 76%
“…We have previously shown that interleukin-5 signaling activates Sox4 transcriptional activity by syntenin associating with the IL5Ra-chain, and further demonstrated syntenin to modulate interleukin-5-induced eosinophil differentiation of hematopoietic stem cells (Geijsen et al, 2001;Beekman et al, 2009). In the current study, we have shown that syntenin can directly stabilize Sox4 expression in a variety of (interleukin-5R negative) tumor cell lines.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations